A real-world pharmacovigilance assessment and literature review of lymphoma development in lipodystrophy - Brown, Rebecca J.; Araujo-Vilar, David; Walkovich, Kelly J.; Barbarosie, Alexandru; Magee, David A.; Akinci, Baris; Oral, Elif A. (Frontiers in endocrinology (Lausanne), 2025)
Metreleptin is a form of leptin replacement therapy used with diet and lifestyle modifications to treat the metabolic complications of leptin deficiency in lipodystrophy, a rare disease characterized by adipose tissue deficiency. Previously, identification of T-cell lymphomas in three metreleptin-treated patients with acquired generalized lipodystrophy (AGL) suggested a possible relationship between metreleptin and lymphoma development. To further investigate this, we performed a real-world pharmacovigilance assessment and literature review to identify lymphomas in patients with lipodystrophy and congenital leptin deficiency (CLD) who were either metreleptin-naïve, or who had previously received/were receiving metreleptin at the time of lymphoma diagnosis. Cases were identified from PubMed, Embase and the Cochrane Library (from database inception through to November 22, 2024), and through review of 11 years post-marketing data from the global safety database (GSD) of the marketing authorization holder for metreleptin. The final analysis set comprised 17 lymphomas in 16 patients reported in 11 published articles and one GSD case report. Twelve lymphomas were recorded in 12 metreleptin-naïve patients - these comprised six T-cell lymphomas (one each in six patients with AGL), three B-cell lymphomas (in two patients with familial partial lipodystrophy and one patient with AGL), and three Hodgkin lymphomas (separately reported in one patient each with generalized lipodystrophy, juvenile-onset dermatomyositis-associated lipodystrophy, and CLD). Five lymphomas were identified in four metreleptin-treated patients, three of whom (all with AGL and T-cell lymphomas) were reported in previously published studies. The remaining metreleptin-treated patient (from the GSD) had generalized lipodystrophy-associated atypical progeroid syndrome and developed a B-cell lymphoma and brain lymphoma following solid organ transplantation and immunosuppressant therapy. All nine T-cell lymphomas occurred in patients with AGL, and additional autoimmune and/or inflammatory disorders were commonly reported in these patients. While a contributory role for metreleptin in lymphoma development in patients with lipodystrophy cannot be excluded, our analysis suggests that lymphoma development may be associated with underlying pathophysiology that also leads to lipodystrophy rather than the pharmacological actions of metreleptin. Our findings support the view that, in some instances, immunoproliferative disorders of T-cells may contribute to syndromes involving autoimmune processes, including AGL.